Correlation Between Findings of Cranial Tomography and the Levels of Cerebrospinal Fluid's Nerve Growth Factor in Hydrocephalic Infants - Erol, Fatih Serhat; Öztürk, Mehmet Birol; Akgün, Bekir; Kaplan, Metin; Çakın, Hakan; İlhan, Necip; Serhatlıoğlu, Selami (Fırat University, 2013)
Objective: To investigate the correlation between the NGF levels in the CSF and brain tomography indexes in preoperative and postoperative evaluations of hydrocephalic infants undergoing ventriculoperitoneal shunt. Material and Method: A total of 27 patients were included. CSF samples were obtained in the during the operation and on the 3rd and 30th postoperative days, and CT evaluations were performed. Results: No correlation was found between the NGF levels in CSF and CCT indexes using the Spearman correlation. The increases of NGF levels on the 3rd postoperative day were significantly higher than those of the peroperative levels (p

Amaç: Ventriküloperitoneal şant uygulanan hidrosefalili bebeklerin ameliyat öncesi ve sonrası değerlendirilmelerinde Beyin Omurilik Sıvısı Sinir Büyüme Faktörü (BOS NGF) düzeyleri ve beyin tomografisi endeksleri arasındaki ilişkiyi araştırmak. Gereç ve Yöntem: Toplam 27 hasta dahil edildi. BT incelemeleri yapıldı ve BOS örnekleri ameliyat sırasında ve ameliyat sonrası 3. ve 30. günlerde alındı. Bulgular: Spearman korelasyonu ile Bilgisayarlı beyin tomografisi (BBT) endekslerinde ve BOS NGF düzeyleri arasında korelasyon bulunamadı. Ameliyat sonrası 3. gün, NGF düzeyi ameliyat öncesi düzeylerine göre anlamlı olarak yüksek bulundu ( p
Hidrosefalik İnfantlarda Kranial Tomografi Bulguları ve Beyin Omurilik Sıvısı Sinir Büyüme Faktörü Arasındaki İlişki